How Effective is Frailty and Comprehensive Geriatric Assessment to Predict the Long-Term Mortality After General Surgery? - Tuna Dogrul, Rana; Dogrul, Ahmet Bulent; Kizilarslanoglu, Muhammet Cemal; Calıskan, Hatice; Balci, Cafer; Sengul Aycicek, Gozde; Ozsurekci, Cemile; Konan, Ali; Halil, Meltem; Cankurtaran, Mustafa; Dogu, Burcu Balam (Acta Medica, 2022)
Introduction: This study investigated the effect of preoperative comprehensive geriatric assessment(CGA) and frailty assessment on long-term mortality. Methods: This study which evaluated a total of 81 older patients underwent the CGA prior to general surgery. Katz ADL, the Lawton Brody IADL, the Mini-Nutrition Assessment test (MNAsf), the Mini-Mental State Examination (MMSE), and Yesavage Geriatric Depression Scale (GDS) were performed. Fried criteria were utilized for the assessment of frailty. The Physiological and Operative Severity Scores for the Enumeration of Mortality and Morbidity (POSSUM) score, and the Charlson Comorbidity Index (CCI) were used for operative risk assessment. The patients were screened for 3-year mortality. Results: The median age of the patients was 71 years (range, 65-84 years). 58.02% of the patients were female and 24.69% were in the frail group. The mortality rate of the frail group was significantly higher than those of the pre-frail and robust groups (p: 0.030). The Cox regression analyses revealed that MMSE (p: 0.020), Physiological Severity Score (PSS) (p: 0.034), BUPA score (p: 0.030) and educational background (p: 0.031) were independently correlated with mortality in Model 1, while MNA (p: 0.003), PSS score (p: 0.080) and educational background (p: 0.002) were correlated with mortality in Model 2. ADL, MMSE, CDT, MNA-SF, Fried score, length of hospital stay, PSS score, and BUPA score were the best predictors of mortality (AUC values: 0.61, 0.74, 0.72, 0.73, 0.69, 0.74, 0.64, and 0.66respectively). Conclusion: The results of the study demonstrated that CGA components and frailty predicted long-term mortality in general surgery patients.